2013
DOI: 10.1155/2013/640673
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Metabolic Comorbidities: Environmental Diseases?

Abstract: Obesity and metabolic comorbidities represent increasing health problems. Endocrine disrupting compounds (EDCs) are exogenous agents that change endocrine function and cause adverse health effects. Most EDCs are synthetic chemicals; some are natural food components as phytoestrogens. People are exposed to complex mixtures of chemicals throughout their lives. EDCs impact hormone-dependent metabolic systems and brain function. Laboratory and human studies provide compelling evidence that human chemical contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 108 publications
3
42
0
1
Order By: Relevance
“…Excessive calorie intake and sedentary life style are major risk factors for obesity and DM but these do not explain the worldwide obesity epidemiology. According to a recent hypothesis, the leading factors for obesity are environmental chemicals, stress, immunologic changes, micronutrient deficit and intestinal microbiota (20). In our series, co-morbidity was also common among obese patients and a significant relationship was demonstrated between number of co-morbidities and endoscopic abnormalities.…”
Section: Grade IIsupporting
confidence: 59%
“…Excessive calorie intake and sedentary life style are major risk factors for obesity and DM but these do not explain the worldwide obesity epidemiology. According to a recent hypothesis, the leading factors for obesity are environmental chemicals, stress, immunologic changes, micronutrient deficit and intestinal microbiota (20). In our series, co-morbidity was also common among obese patients and a significant relationship was demonstrated between number of co-morbidities and endoscopic abnormalities.…”
Section: Grade IIsupporting
confidence: 59%
“…On the other hand, it is known that certain environmental factors influence the epigenetic programming in cells through chemical nucleotide modification [10,11]. Different non-nutritional risk factors such as oxygen availability and oxidative stress, together with obesity are potentially involved in these epigenetic modifications [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…High ROS production and the decrease in antioxidant capacity observed in obesity can then damage various cellular structures and lead to various abnormalities including endothelial dysfunction favoring atherosclerotic disease [3] insulin resistance [4,18], metabolic syndrome [4,[22][23][24], type 2 diabetes, and cancer. Recently, it has been suggested that increased oxidative stress and inflammation in obesity also enhance aging processes [24].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is now the sixth most important risk factor contributing to the overall burden of disease worldwide [2]. Substantial literature shows that overweight and obesity are major causes of co-morbidities, metabolic syndrome, including type 2 diabetes mellitus, cardiovascular diseases, various cancers, and other health problems, which can lead to further morbidity and mortality [3,4].…”
Section: Introductionmentioning
confidence: 99%